2013
DOI: 10.1088/0004-6256/146/1/12
|View full text |Cite
|
Sign up to set email alerts
|

Kronoseismology: Using Density Waves in Saturn's C Ring to Probe the Planet's Interior

Abstract: Saturn's C ring contains multiple spiral patterns that appear to be density waves driven by periodic gravitational perturbations. In other parts of Saturn's rings, such waves are generated by Lindblad resonances with Saturn's various moons, but most of the wave-like C-ring features are not situated near any strong resonance with any known moon. Using stellar occultation data obtained by the Visual and Infrared Mapping Spectrometer (VIMS) onboard the Cassini spacecraft, we investigate the origin of six unidenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 21 publications
12
123
2
Order By: Relevance
“…Re-analyzing the original six waves with this larger data set yielded essentially the same results as our previous analysis (compare the relevant entries in Table 5 with Table 4 The first wave we will consider here is the one designated W83.63 in Colwell et al (2009) (it is also called h in Rosen et al (1991) and wave 18 in Baillié et al (2011)). An example profile of this wave is shown in Figure 3, where it is compared with two nearby waves examined by Hedman & Nicholson (2013). Note this wave is found in a low opticaldepth region between three waves (W82.00, W82.06 and W82.21) that Hedman & Nicholson (2013) identified as m = −3 and another wave (W84.64) that appears to have m = −2 (see Figure 1).…”
Section: Selecting Features To Examinementioning
confidence: 93%
See 3 more Smart Citations
“…Re-analyzing the original six waves with this larger data set yielded essentially the same results as our previous analysis (compare the relevant entries in Table 5 with Table 4 The first wave we will consider here is the one designated W83.63 in Colwell et al (2009) (it is also called h in Rosen et al (1991) and wave 18 in Baillié et al (2011)). An example profile of this wave is shown in Figure 3, where it is compared with two nearby waves examined by Hedman & Nicholson (2013). Note this wave is found in a low opticaldepth region between three waves (W82.00, W82.06 and W82.21) that Hedman & Nicholson (2013) identified as m = −3 and another wave (W84.64) that appears to have m = −2 (see Figure 1).…”
Section: Selecting Features To Examinementioning
confidence: 93%
“…For the sake of completeness, we will provide a summary of our analysis methods, and refer the reader to Hedman & Nicholson (2013) for more details on these techniques.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic idea is that wave features in Saturn's C rings could be created by resonant interactions with fundamental (f ) oscillation modes (i.e., radial order n = 0), since these modes perturb the internal density profile and, therefore, the external gravity field. Twenty years later, observations of stellar occultations of stars by the rings made with Cassini showed that density-wave structures detected in the C-ring were compatible with resonances due to Saturn f -modes [30][31][32]. These observations are the indirect evidence of these wave forcings [32].…”
Section: Seismology and Giant Planetsmentioning
confidence: 93%